1997
DOI: 10.1093/oxfordjournals.aje.a009115
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Toenail Selenium and Risk of Acute Myocardial Infarction in European Men: The EURAMIC Study

Abstract: The association between selenium status and risk of acute myocardial infarction was examined in a multicenter case-control study in 10 centers from Europe and Israel in 1991-1992. Selenium in toenails was assessed for 683 nonfatal male cases with first acute myocardial infarction and 729 controls less than 70 years of age. Median toenail selenium content was 0.553 /xg/g for cases and 0.590 jxg/g for controls. After adjustment for age, center, and smoking, the odds ratio for myocardial infarction in the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…Although previous studies have assessed the selenium content in toe nails, which is 9 -15% lower than that of fingernails (Baskett et al, 1995), selenium concentrations in these British men are still somewhat lower than those reported in North American populations (Yoshizawa et al, 1998;Ghadirian et al, 2000;Helzlsouer et al, 2000) and are comparable with other European populations (Kardinaal et al, 1997;van den Brandt et al, 2003). It is well established that the selenium content of European soils is low and that dietary intake has been gradually declining due to a reduction in imported selenium-rich wheat from the US and Canada, together with a general decline in cereal consumption (Rayman, 1997).…”
Section: Discussionmentioning
confidence: 51%
“…Although previous studies have assessed the selenium content in toe nails, which is 9 -15% lower than that of fingernails (Baskett et al, 1995), selenium concentrations in these British men are still somewhat lower than those reported in North American populations (Yoshizawa et al, 1998;Ghadirian et al, 2000;Helzlsouer et al, 2000) and are comparable with other European populations (Kardinaal et al, 1997;van den Brandt et al, 2003). It is well established that the selenium content of European soils is low and that dietary intake has been gradually declining due to a reduction in imported selenium-rich wheat from the US and Canada, together with a general decline in cereal consumption (Rayman, 1997).…”
Section: Discussionmentioning
confidence: 51%
“…However, about six other studies have not shown a clear association between cardiovascular risk and low Se, although these studies differ from the previously mentioned studies in having included few or no subjects with low Se status (Salvini et al 1995;Neve, 1996). That a low Se status may be relevant was suggested by the findings of Kardinaal et al (1997) in the ten-centre EURAMIC study, in which a significant inverse association between toenail Se levels and risk of myocardial infarction was shown only for Germany, the centre with the lowest Se status (odds ratio 0-62 (95% CI 0-42, 0-91)). Thus, the effect may only be apparent in populations of low Se status, lower than the levels present in the USA and a large part of Europe.…”
Section: Health Effects Related To the Role Of Selenium As Antioxidantmentioning
confidence: 89%
“…4,52 That a low Se status may be relevant was suggested by the findings of Kardinaal and colleagues in the 10-centre EURAMIC study where a significant inverse association between toenail Se levels and risk of myocardial infarction was shown only for the centre with the lowest Se (Germany). 53 Thus the effect may only be apparent in populations of low Se status, lower than the levels obtaining in the US and a large part of Europe. The disparity between studies may also be explained to some extent by the status of other antioxidants such as vitamin E, which may compensate for a deficiency in Se in protection against atherosclerosis.…”
Section: Thyroid Functionmentioning
confidence: 97%
“…The disparity between studies may also be explained to some extent by the status of other antioxidants such as vitamin E, which may compensate for a deficiency in Se in protection against atherosclerosis. 53 A further factor to be taken into consideration when assessing these studies is that atherosclerosis is an inflammatory state and will provoke the acute phase response to a degree related its severity. Being an acute phase reactant, 54 some fall in plasma Se concentration might be expected in subjects suffering from atherosclerosis, even before the occurrence of an event.…”
Section: Thyroid Functionmentioning
confidence: 99%